SUPPORTING YOUNG FARMERS AND THE SUSTAINABILITY OF RURAL REGIONS. CASE STUDY - OLT COUNTY, ROMANIA - Alina Mariana P. POPA (PODARU); Adrian TUREK RAHOVEANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The support system for young farmers within the CAP, through the large volume of projects, has one of the strongest effects on the development of Romanian agriculture. In Romania, support for young farmers under the CAP has been introduced since 2007, with Romania's accession to the European Union. The scheme provides financial support to people under the age of forty who want to start an agricultural business. Moreover, the support measure for the establishment of young farmers was continued in the 2014-2020 programming period, the intensity of support being even higher. Other non-direct support measures for young farmers through National Rural Development Program (NRDP) funding have also served to change future generations of farmers. The purpose of this paper is to present the results of a survey in Olt County that considered the link between the sustainable development of the county region through the actors that make it up: a new generation of young farmers. As a main tool of the analysis, a questionnaire was completed and applied to 170 beneficiaries of sub-measure 6.1. "The installation of the young farmer". The implementation of the questionnaires resulted in a series of benefits that young farmers obtained, but also the difficulties they encounter in their activity. We could see that the financial benefits obtained by young farmers through sub-measure 6.1. from the NRDP shows that this system contributes greatly to supporting the level of development of agricultural holdings they own, with positive long-term results on increasing their incomes, improving the quality of life. According to a significant percentage of the 170 farmers participating in the study, one problem they face is mainly related to finding new markets. Many of those interviewed do not have large quantities of agricultural products in order to enter the free market, to be able to negotiate a competitive price, being at the beginning of activity in this field. That is why some consider that a solution for capitalization through cooperatives or producer associations would be a beneficial solution in the future.